Efficacy of eco-smart insecticides against certain biological stages of jasmine moth, Palpita unionalis Hb. (Lepidoptera: Pyralidae) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The efficacy of six eco-smart insecticides, Dipel 2x 6.4% WP (Bacillus thuringensis AI), Biofly 100% WP (Beauvaria bessiana AI), Radiant 12% SC (Saccharopolyspora spinosa AI), Mectin 1.8% EC (Streptomyces avermitilis AI), Nimbecidine 0.03% EC (Azadirachtin AI) and Bio-Power 50% EC (Beauvaria bessiana AI), were tested against eggs, larvae and pupae of the jasmine moth, Palpita unionalis Hb. and its parasitoid Apanteles syleptae under laboratory conditions. Data indicated that all tested insecticides had ovicidal activity against P. unionalis. Mectin was the most toxic among the tested insecticides against the egg stage, followed by Radiant or Dipel 2x, and their respective values of LC50 were 0.005 cm/l, 0.006 cm/l and 0.055 g/l. Dipel 2x was the most toxic insecticide to the 1st instar larvae of P. unionalis, whereas Mectin was the most toxic to both the 3rd and 5th instar larvae. Also, the results revealed that Mectin was the most effective against the pupal stage, followed descendingly by Radiant and Dipel 2x. The toxicity index values showed a superior efficiency of Mectin at LC50 (100%) against eggs, 3rd and 5th instar larvae, and pupal stage, whereas Dipel 2x showed such superior efficiency at LC50 (100%) only against 1st instar larvae. The results showed that the percents of pupation and emergence of moths were significantly different in all treatments compared to control, while deformed pupae and malformed adults were insignificantly different when fifth instar larvae were treated with the tested insecticides. Moreover, the rate of P. unionalis adult emergence from treated pupae was concentration-dependent and significant differences were found between insecticide treatments and control. Generally, Mectin, Radiant and Dipel 2x caused the highest impacts on adult emergence and malformed adults percentages. Regarding the toxicity of insecticides to the endoparasitoid A. syleptae, the treated cocoons developed to adult stages with no significant differences compared to control. Meanwhile, the longevity of the emerged parasitoid adults did not differ among the insecticides treatments and control.
Keywords: Palpita unionalis; Apanteles syleptae; Botanical insecticides; Microbial pesticides; Toxicity